Comparative Analysis of Semantic Polarity in “Gila” and “Atama ga Okashii” - Alifah Dini Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
This study aims to compare the meaning polarity of the Indonesian word gila and the Japanese expression atama ga okashii through a descriptive comparative approach. The data consist of 25 items for Indonesian and 27 items for Japanese, collected from various authentic sources, including news articles, social media, blogs, and online corpora. Polarity analysis follows the positive, neutral, and negative classification framework based on Tarigan (1985) and Inui et al. (2008). The results show that both expressions are dominated by negative polarity -gila at 56% and atama ga okashii at 55.6%. Despite similar quantitative distributions, a significant qualitative difference was found in their semantic extension ranges. The word gila demonstrates higher semantic flexibility, extending into culinary, informal social identity, and appreciative domains -reflecting a process of amelioration and semantic broadening. In contrast, atama ga okashii maintains its stigmatic connotation more consistently and does not exhibit equivalent semantic extension. These findings indicate that lexical equivalence across languages does not necessarily reflect pragmatic equivalence, as the meaning of an expression is strongly shaped by the social and cultural norms of its speech community.